2023
DOI: 10.3389/fphar.2023.1136897
|View full text |Cite
|
Sign up to set email alerts
|

Sanghuangporus sanghuang extract extended the lifespan and healthspan of Caenorhabditis elegans via DAF-16/SIR-2.1

Abstract: Sanghuangporus Sanghuang is a fungus species. As a traditional Chinese medicine, it is known for antitumor, antioxidant and anti-inflammatory properties. However, the antiaging effect of S. Sanghuang has not been deeply studied. In this study, the effects of S. Sanghuang extract (SSE) supernatants on the changes of nematode indicators were investigated. The results showed that different concentrations of SSE prolonged the lifespans of nematodes and substantially increased these by 26.41%. In addition, accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The accumulation of ROS is considered to be one of the important causes of aging in C. elegans ( Dong et al, 2023 ). The method of C. elegans was used for the determination of ROS levels in S. kraussei cells, and H 2 DCFH-DA was also used for the determination of ROS levels in S. kraussei cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The accumulation of ROS is considered to be one of the important causes of aging in C. elegans ( Dong et al, 2023 ). The method of C. elegans was used for the determination of ROS levels in S. kraussei cells, and H 2 DCFH-DA was also used for the determination of ROS levels in S. kraussei cells.…”
Section: Resultsmentioning
confidence: 99%
“…The mitochondrial free radical theory of aging (MFRTA) is one of the most important theories of aging and proposes that aging is caused by the destruction of macromolecules by mitochondrial ROS. Therefore, ROS accumulation is considered to be one of the important causes of senescence, and decreasing ROS production can effectively delay aging (Dong et al, 2023). Normally, with increased age, ROS cause oxidative damage to DNA, proteins and lipids, ROS levels rise, damage accumulates, cell dysfunction occurs, and Frontiers in Physiology frontiersin.org the aging process accelerates, which leads to a shortened lifespan (Qi et al, 2021).…”
Section: Gpc Enhanced Antioxidant Enzyme Activities In S Kraussei 0657lmentioning
confidence: 99%
See 1 more Smart Citation
“…By treating the Caenorhabditis elegans nematodes with 10, 25, and 50 mg/mL of S. sanghuang extracts to study their effects on lifespan in vivo under the influence of 50 μM 5-fluoro-20-deoxyuridine (FUDR), Dong et al discovered that, after 14 days, the 25 mg/mL group showed a 26.41% increase in the mean lifespan compared to the control group (20.52 ± 0.34 days and 16.23 ± 0.36 days, respectively) [ 239 ]. They also inferred that the antiaging effect was achieved at the mRNA level, such as increased transcriptional regulators of daf-16 and sir-2.1, and that the lifespan was prolonged through the insulin/IGF-1 signaling pathway [ 239 ]. Their results, for the first time, revealed the related mechanisms in the antiaging effect of Sanghuang components.…”
Section: Health-improving Effectsmentioning
confidence: 99%